Evaluation of Nutrition and Eating Habits in Children and Adolescents Practicing Football in a Sports Club in Bydgoszcz, Poland - Ameryk, Monika; Pujanek, Małgorzata; Augustyniak, Agnieszka; Szamocka, Małgorzata; Świątkowski, Maciej (Journal of Education, Health and Sport, 2016)
Abstract Proper diet is important for children and adolescents practicing sports, providing nutrients for the correct growth, optimal performance and recovery. Purpose: The study evaluated the diet and eating habits of children and adolescents practicing football. Methods: The study involved 100 boys (aged 11–16). Eating habits and consumption of 33 products were assessed using a modified KomPAN questionnaire. Subsequently, indices of healthy and unhealthy diet were determined. Results: Only 30% respondents ate five meals per day and 16% kept fixed meal times. Almost 30% had a snack once daily, 90% ate fast food once a week, and 88% added sugar to beverages. One in ten ate sweets several times per week, while 20%—once daily. 86% ate fish once a week. 52% and 4% ate white and dark bread several times per day. Only 20% had buckwheat several times per week. White and red meat was eaten several times per week by 66.3% and 35.6%, while fish by only 5.7%. Only 20% had a moderate index of healthy diet and 90% had a low index of unhealthy diet. Conclusions: Education of young footballers in nutrition is necessary to correct their eating habits and improve physical performance.